A Long-Term Electricity Consumption Model adapted from the MMM-ARCH-M Framework for Strategic Greenhouse Gas Emission Reduction towards Smart City Goals in Thailand - Sutthichaimethee, Pruethsan; Sa-Ngiamvibool, Worawat; Wattana, Buncha; Luo, Jianhui; Wattana, Supannika (Engineering, Technology & Applied Science Research, 2025)
This research aims to identify the factors for formulating management strategies that enhance energy consumption efficiency in the electricity sector to achieve the long-term goal of reducing greenhouse gas emissions and transitioning towards Smart City Thailand. The research employs a quantitative approach by developing an advanced model known as the Moderated Mediation Model based on Autoregressive Conditionally Heteroscedastic in Mean (MMM-ARCH-M). This model incorporates white noise and the best model methodology, serving as a decision-making tool for future national development. It fills gaps found in previous models, yielding more accurate and precise future forecasts. Additionally, the model demonstrates high validity, making it applicable to other sectors. The research findings reveal that the government needs to establish the most appropriate new scenario policies to develop long-term (2025-2044) national management strategies under sustainability policies aimed at achieving Smart City Thailand. The research identifies critical indicators that need to be immediately and urgently implemented nationwide through enforceable legislation. These indicators include clean technology, waste biomass, renewable energy, green material rate, and biomass energy. If the government adopts these indicators for national management, the total energy consumption growth rate (2044/2025) will increase by only 90.59%, which is lower than the defined carrying capacity of 150.45%. Furthermore, CO2 gas emissions are found to decrease by 35.09%, with CO2 emissions reaching 42.50 Mt CO2 Eq. by 2044, which is within Thailand’s carrying capacity limit of 50.07 Mt CO₂ Eq. Thus, this model is highly beneficial as a decision-making tool for national management, supporting the realization of Smart City Thailand and ensuring long-term sustainability.